2013
DOI: 10.1016/j.bmcl.2013.08.095
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 15-methylene-eburnamonine from (+)-vincamine, evaluation of anticancer activity, and investigation of mechanism of action by quantitative NMR

Abstract: The biological role of installing a critical exocyclic enone into the structure of the alkaloid, (−)-eburnamonine, and characterization of the new chemical reactivity by quantitative NMR without using deuterated solvents are described. This selective modification to a natural product imparts potent anticancer activity as well as bestows chemical reactivity toward nucleophilic thiols, which was measured by quantitative NMR. The synthetic strategy provides an overall conversion of 40%. In the key synthetic step,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…20 Additional evaluation of 1 and 3 side-by-side in MDA-MB-231 (breast cancer), 20 LNCaP (prostate cancer), RPMI-8226 (myleoma), U266 (myeloma), and KMS-12BM (myeloma) cell lines 21 is shown in Table 1. To investigate further the cytotoxicity of 3 in leukemia cells, primary ALL, AML, and CLL cells were treated with varying doses of 3 and cell viability was assessed by calcein AM staining (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…20 Additional evaluation of 1 and 3 side-by-side in MDA-MB-231 (breast cancer), 20 LNCaP (prostate cancer), RPMI-8226 (myleoma), U266 (myeloma), and KMS-12BM (myeloma) cell lines 21 is shown in Table 1. To investigate further the cytotoxicity of 3 in leukemia cells, primary ALL, AML, and CLL cells were treated with varying doses of 3 and cell viability was assessed by calcein AM staining (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…20 Subsequent studies showed that this functional group is not only required for activity but also susceptible to conjugation by reactive thiols. 21 In a similar fashion, this functional group imparts biological activity to another natural product, parthenolide ( 4 ), and this compound has been shown to eliminate LSCs by increasing intracellular reactive oxygen species (ROS) 8 and depleting intracellular glutathione levels. 26 To examine if the anti-leukemia properties of 3 were also related to these processes, we co-treated cells with 3 and the antioxidant, glutathione (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tetrahydrocarbazole ring can be considered as an isostere to b-carboline ring which is present in many naturally occurring anticancer agents, such as the vinca alkaloids, vincamine (III) and (-)-eburnamonine (IV) (Figure 1) isolated from the Madagascar periwinkle (Catharanthus roseus) [33][34][35] . Although (-)-eburnamonine (IV) was devoid of anticancer activity even at the high dose of 100 M, its synthetic analogue 15-methylene-eburnamonine (V) displayed in vitro micromolar activity against prostate and myeloma cell lines 36 . Furthermore, the marine alkaloid Eudistomin K (VI), isolated from the Caribbean ascidian Eudistoma olivaceum, demonstrated potent antitumor activity against L-1210, A-549, HCT-8 and P-388 cell lines 37,38 .…”
Section: Introductionmentioning
confidence: 99%